Further insights into the molecular complexity of the human sinus node – The role of 'novel' transcription factors and microRNAs. (November 2021) - Aminu, Abimbola J.; Petkova, Maria; Atkinson, Andrew J.; Yanni, Joseph; Morris, Alex D.; Simms, Robert T.; Chen, Weixuan; Yin, Zeyuan; Kuniewicz, Marcin; Holda, Mateusz K.; Kuzmin, Vladislav S.; Perde, Filip; et al.
Abstract: Research purpose: The sinus node (SN) is the heart's primary pacemaker. Key ion channels (mainly the funny channel, HCN4) and Ca 2+ -handling proteins in the SN are responsible for its function. Transcription factors (TFs) regulate gene expression through inhibition or activation and microRNAs (miRs) do this through inhibition. There is high expression of macrophages and mast cells within the SN connective tissue. 'Novel'/unexplored TFs and miRs in the regulation of ion channels and immune cells in the SN are not well understood. Using RNAseq and bioinformatics, the expression profile and predicted interaction of key TFs and cell markers with key miRs in the adult human SN vs. right atrial tissue (RA) were determined. Principal results: 68 and 60 TFs significantly more or less expressed in the SN vs. RA respectively. Among those more expressed were ISL1 and TBX3 (involved in embryonic development of the SN) and 'novel' RUNX1-2, CEBPA, GLI1-2 and SOX2. These TFs were predicted to regulate HCN4 expression in the SN. Markers for different cells: fibroblasts (COL1A1), fat (FABP4), macrophages (CSF1R and CD209), natural killer (GZMA) and mast (TPSAB1) were significantly more expressed in the SN vs. RA. Interestingly, RUNX1-3, CEBPA and GLI1 also regulate expression of these cells. MiR-486-3p inhibits HCN4 and markers involved in immune response. Major conclusions: In conclusion, RUNX1-2, CSF1R, TPSAB1, COL1A1 and HCN4 are highly expressed in the SN but not miR-486-3p. Their complex interactions can be used to treat SN dysfunction such as bradycardia. Interestingly, another research group recently reported miR-486-3p is upregulated in blood samples from severe COVID-19 patients who suffer from bradycardia.